Financial Accelerator in National Private Banks During COVID-19 Pandemic - Berhan, Dennis; Hasid, Zamruddin; Wardhani, Wirasmi (Asian Journal of Management Analytics, 2024)
This research aims to investigate the effect of liquidity, credit risk, and bank size on the financial accelerator in National Private Banks registered with the Indonesian Financial Services Authority during the period of 2019-2022. The research design uses a causal approach. The population of this study is National Private Banks in Indonesia that are registered by Indonesian Financial Services Authority throughout the research period, 2019-2022, with the total population of 68 banks. This study uses purposive sampling method. There are 56 companies as samples of this study, resulting 224 financial statement data. The data is analyzed by using the Generalized Method of Moments (GMM).The research findings indicate that liquidity has a negative and significant impact on the financial accelerator effect in National Private Banks registered with the Indonesian Financial Services Authority during the period 2019-2022 (significance value 0.041 < α = 0.05).Credit risk also has a negative and significant impact on the financial accelerator effect in these banks during the same period (significance value 0.015 < α = 0.05). Bank size shows a negative but statistically insignificant influence on the financial accelerator effect in National Private Banks registered with the OJK during the period 2019-2022 (significance value 0.865 > α = 0.05).